2019
DOI: 10.3847/1538-4357/ab4a7c
|View full text |Cite
|
Sign up to set email alerts
|

The MOSDEF Survey: A Census of AGN-driven Ionized Outflows at z = 1.4–3.8

Abstract: Using data from the MOSFIRE Deep Evolution Field (MOSDEF) survey, we present a census of AGN-driven ionized outflows in a sample of 159 AGNs at 1.4 ≤ z ≤ 3.8. The sample spans AGN bolometric luminosities of 10 44−47 erg s −1 and includes both quiescent and star-forming galaxies extending across three orders of magnitude in stellar mass. We identify and characterize outflows from the Hβ, [OIII], Hα and [NII] emission line spectra. We detect outflows in 17% of the AGNs, seven times more often than in a mass-matc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 122 publications
2
55
0
Order By: Relevance
“…Errors in line fluxes were derived by allowing the spectra to vary 500 times according to the error spectra and remeasuring the line fluxes from these realizations. For this study, active galactic nuclei (AGNs) were excluded based on the IR, X-ray, and rest-frame optical line flux criteria as described in Coil et al (2015), Azadi et al (2017Azadi et al ( , 2018, and Leung et al (2019). Further details on target selection, observations, spectroscopic data reduction, slit loss corrections, and line flux measurements are provided in several papers discussing results from the MOSDEF survey (e.g., Kriek et al 2015;Reddy et al 2015).…”
Section: Line Flux Measurementsmentioning
confidence: 99%
“…Errors in line fluxes were derived by allowing the spectra to vary 500 times according to the error spectra and remeasuring the line fluxes from these realizations. For this study, active galactic nuclei (AGNs) were excluded based on the IR, X-ray, and rest-frame optical line flux criteria as described in Coil et al (2015), Azadi et al (2017Azadi et al ( , 2018, and Leung et al (2019). Further details on target selection, observations, spectroscopic data reduction, slit loss corrections, and line flux measurements are provided in several papers discussing results from the MOSDEF survey (e.g., Kriek et al 2015;Reddy et al 2015).…”
Section: Line Flux Measurementsmentioning
confidence: 99%
“…Among AGN surveys, Leung et al (2019) target opticallyselected AGN using single-slit spectroscopy from the MOS-DEF survey with bolometric luminosities in the range 10 44 −10 47 erg s −1 at z ∼ 1.4-3.8 and find outflows in 17% of their sample of ∼160 AGN. Moreover, it is claimed that the ionised gas mass outflow rates correlate positively with the luminosity of the AGN, but do not depend on the galaxy stellar mass, which is in contrast with the findings of Förster Schreiber et al (2018) concerning star forming galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…A number of observational campaigns such as the WISSH survey of hyper-luminous QSOs (Bischetti et al 2017), the SUPER survey (Circosta et al 2018), the KASH-z survey of X-ray selected AGN (Harrison et al 2016), found ubiquitous ionised outflows at these redshifts. Moreover, the SINS zC-SINF plus KMOS3D (Förster Schreiber et al 2018 and the MOSDEF (Leung et al 2019) surveys found that the incidence of fast ionised outflows increases with stellar mass jointly with AGN fraction, and so their incidence in AGN is independent on stellar mass.…”
Section: Outflows From High To Low Redshiftmentioning
confidence: 99%